Предмет: Алгебра,
автор: Аноним
Ребят, пожалуйста, помогите решить)
Приложения:
Ответы
Автор ответа:
0
1)(1-x^2/y^2)(y-x)/xy=(y^2-x^2)*xy/y^2(y-x)=x(y+x)/y
2)(x^2-y^2-2x^28*y-x)/x(x-y)*(x^2+y^2)=-(x^2+y^2*(y-x)/x(x-y)*(x^2+y^2)=1/x
1/x=1/x
2)(x^2-y^2-2x^28*y-x)/x(x-y)*(x^2+y^2)=-(x^2+y^2*(y-x)/x(x-y)*(x^2+y^2)=1/x
1/x=1/x
Автор ответа:
0
Спасибо!
Автор ответа:
0
Первое . Больше не смогла...
Приложения:
Похожие вопросы
Предмет: Математика,
автор: asdfg20200809
Предмет: Алгебра,
автор: chiterite02
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Обществознание,
автор: Вика515
Предмет: Алгебра,
автор: ibyf